2010
DOI: 10.1021/ja910264z
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Increases Nucleosome Compaction and Rigidity

Abstract: Cytosine methylation on CpG dinucleotides is an essential epigenetic modification in eukaryotes. How DNA methylation modulates nucleosome structure and dynamics has been a long standing question. We implemented a single molecule method to monitor effects of DNA methylation on the structure and dynamics of mononucleosomes. Our studies show that DNA methylation induces a more compact and rigid nucleosome structure, providing a physical basis for how DNA methylation might contribute to regulating chromatin struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
202
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(218 citation statements)
references
References 15 publications
13
202
2
1
Order By: Relevance
“…Perhaps because the sensor somewhat resembles the structure of actin dimers, the actin probe AcpA expresses well and labels f-actin efficiently, presumably at random locations. For imaging purposes, we found that, as previously published, polarized FRET (16)(17)(18) reduces bleed-through corrections and provides increased contrast.…”
supporting
confidence: 81%
“…Perhaps because the sensor somewhat resembles the structure of actin dimers, the actin probe AcpA expresses well and labels f-actin efficiently, presumably at random locations. For imaging purposes, we found that, as previously published, polarized FRET (16)(17)(18) reduces bleed-through corrections and provides increased contrast.…”
supporting
confidence: 81%
“…We then a global genomic scale (particularly at repetitive sequences) and hypermethylation at CGIs. 27 CpG methylation may induce a more compact and rigid nucleosome structure 67 that would significantly affect the CGIs, which normally are relatively nucleosome-deficient and permissive for TF binding. 62 Perhaps more significantly, hypomethylation of the bulk of the genome might open access to many potential binding sites that are not accessible in normal cells.…”
Section: Resultsmentioning
confidence: 99%
“…3) (36). Nucleosomes containing the 147-bp DNA displayed one major band, some minor amounts of higher molecular weight species, and free DNAs.…”
Section: Dna Fragment Preparation and Reconstitution Of Nucleosomes Umentioning
confidence: 99%